Constructing the Meaning of Achieving Life Success in Broken Home Survivors in Virtual Communities - Lestari, Anggita; Nurfaizy, Ramadhan; Reza, Faisal; Midaya P, G Guci Derry (Yayasan Sinergi Kawula Muda, 2024)
The phenomenon of broken homes has been widely discussed in the current social media era along with the increasing public awareness of mental health. This study explores the lives of people who have gone through the difficult experience of a broken home. It focuses on those who listen to the podcast